Observation and Simulation of Mutual Approximations between Five Main Uranian Satellites - Jian Chen; Hao-Ran Song; Ye Yuan; Fan Li; Yan-Ning Fu; Tian-Rui Sun; Yu-Xi Jiang (The Astronomical Journal)
Mutual approximation is an emerging method for obtaining high-precision astrometric measurements of natural satellites and asteroids. We used the 80 cm YaoAn High Precision Telescope to observe mutual approximation events of the main Uranian satellites during the period from 2021 to 2023. The average of internal errors along the directions of apparent relative motion and position are 20.0 and 5.1 mas, respectively. On the other hand, the rms of differences between observational results and the Jet Propulsion Laboratory ephemeris along the direction of apparent relative motion and position are 42.5 and 20.6 mas, respectively. We also investigated the factors affecting astrometric precision and found two simple indicators to exclude the invalid mutual approximation events, i.e., the events that do not contribute to precision enhancement. One indicator is the impact parameters divided by the difference of two satellites’ apparent semimajor axes; the other is the apparent relative velocity divided by the difference of their apparent orbital velocities. The resulting quotients of all invalid events are significantly larger than 1.1. Simulations confirm that the indicators are suitable for all the main Uranian satellites' mutual approximation events in recent years and the near future. Consequently, it is recommended to exclude invalid events from future observation campaigns by using the two indicators.